2021
DOI: 10.1038/s41598-021-01324-0
|View full text |Cite
|
Sign up to set email alerts
|

Integrative epigenomics in Sjögren´s syndrome reveals novel pathways and a strong interaction between the HLA, autoantibodies and the interferon signature

Abstract: Primary Sjögren’s syndrome (SS) is a systemic autoimmune disease characterized by lymphocytic infiltration and damage of exocrine salivary and lacrimal glands. The etiology of SS is complex with environmental triggers and genetic factors involved. By conducting an integrated multi-omics study, we confirmed a vast coordinated hypomethylation and overexpression effects in IFN-related genes, what is known as the IFN signature. Stratified and conditional analyses suggest a strong interaction between SS-associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 85 publications
0
25
0
Order By: Relevance
“…Recently, the evolutionarily conserved Wnt pathway, which regulates crucial aspects of cell fate determination during embryogenesis, has also been reported to increase skin fibrosis in SSc patients via epigenetic dysregulation; treatment with 5-azacitidine (5-Aza) abolishes the fibrotic phenotype [175][176][177]. Noteworthy, in peripheral blood cells of SS patients, the same hypomethylation of the type I IFN signalling pathwayassociated genes is coupled with hypermethylation of RUNX1 and Foxp3 genes, important in the control of Treg cell generation and function [178,179] (Table 1).…”
Section: The Epigenetic Code Of Autoimmune Disordersmentioning
confidence: 99%
“…Recently, the evolutionarily conserved Wnt pathway, which regulates crucial aspects of cell fate determination during embryogenesis, has also been reported to increase skin fibrosis in SSc patients via epigenetic dysregulation; treatment with 5-azacitidine (5-Aza) abolishes the fibrotic phenotype [175][176][177]. Noteworthy, in peripheral blood cells of SS patients, the same hypomethylation of the type I IFN signalling pathwayassociated genes is coupled with hypermethylation of RUNX1 and Foxp3 genes, important in the control of Treg cell generation and function [178,179] (Table 1).…”
Section: The Epigenetic Code Of Autoimmune Disordersmentioning
confidence: 99%
“…Although the aetiology of SS is unknown, it is considered that different factors, such as environmental, genetic and epigenetic, contribute to the disease pathogenesis. In this context, several studies [ 40 , 41 , 42 , 43 ], have focused on finding genetic and epigenetic factors that could be associated with SS. Transcriptomics, genome-wide association studies (GWAS) to identify genomic variants that are statistically associated with a risk of suffering the disease and epigenetic studies to determine whether gene expression is active or inactive based on DNA methylation are widely used nowadays.…”
Section: Resultsmentioning
confidence: 99%
“…The first gene, ATP10A , encoded 1 of the 5 P4 ATPase that requires interaction with transmembrane protein 30A to exit from the endoplasmic reticulum to the plasma membrane. ATP10A was recently linked to autoimmunity, as one study demonstrated that methylation qualitative trait loci regulated the methylation of the ATP10A gene in blood samples from patients with primary SS ( 34 ). Since this enzyme mainly transports 2 aminophospholipids: phosphatidylserine and phosphatidylethanolamine, which may be the target of minor autoantibodies in antiphospholipid syndrome (APS) ( 35 ), it is reasonable to speculate that there is a link between the presence of antiphospholipid antibodies and the increase in ATP10A transcript.…”
Section: Discussionmentioning
confidence: 99%